Perancangan Aplikasi Pembelajaran Bahasa Jepang Berbasis Android - Mohammad Febrian Sudi Prasetya; Jaka Sutresna (CV. Multi Kreasi Media, 2023)
In the midst of this digital era, the rapid development of information technology, especially in the world of education, is very important for human needs in learning and teaching activities by utilizing this technology. One of them is by using various learning media such as android-based learning applications. Learning applications are programs that function as tools, materials or techniques used in teaching and learning activities with the intention that the process of educational communication interaction between teachers and students can take place effectively and efficiently. At SMK Taruna Terpadu 1 there are various problems, one of which is that teachers lack interactive learning media for their students, therefore the solution to the problem is to create an Android-based Japanese language learning application, with Android-based teachers and students can access it anywhere. Making this application using the javascript programming language, then SQLite as a local database, android studio as an android application development. Testing this application is done using the black box method by compiling a list of test cases and the white box method by compiling a flow graph. Blackbox testing is carried out to test whether the system developed is in accordance with what is stated in the functional system specificationsThe results of the application of this application are expected to help the learning process of teachers and students at the Taruna Terpadu 1 Vocational School.